Diseño de una solución para integrar la red de telefonía IP con la red de radiocomunicación de la Central Eólica Villonaco mediante tecnología RoIP. - Paute Cuenca, Nelson Gustavo (2023)
The degree work consists of the design of a solution proposal for the integration of the VoIP (Voice over Internet Protocol) network of IT (Information Technology) with the radio communication network of the Villonaco Wind Power Plant of CELEC EP, through the RoIP (Radio Over Internet Protocol) technology, to extend the communications of the Wind Farm with the operation room, headquarters, maintenance and administrative offices in the city of Loja, considering high levels of scalability, security and minimizing implementation costs, taking advantage of the current technology and data network. The technological infrastructure of the institution, communication channels, current bandwidth and availability, equipment consumption, QoS analysis, and design will be analyzed to prioritize VoIP in the central network. Subsequently, market equipment with RoIP technology will be analyzed, evaluating its features and performance through a comparison of their datasheet, which will finally allow me to determine which is the most suitable solution for the communication needs in the Villonaco Wind Power Plant. Keywords: • VoIP (Voice over Internet Protocol), • IT (Information Technology), • RoIP (Radio Over Internet Protocol), • QoS (quality of service).